Scalable quality of service (QoS) over broadband internet and next generation mobile network - Zaw, Min Naing (2008)
The increasing need of providing QoS over broadband Internet and mobile network has driven the intensification of the research efforts in this area. The thesis mainly focuses on modeling and performance analysis of scalable QoS over broadband Internet and MPLS based mobile network.